Productivity and Market Power: The Case of Manufacturing firms of Peru 2002-2019 - (:unkn) unknown (My University, 2026)
As many advanced economies (IMF 2019, De Loecker & Eeckhout 2021), firms’ market power and concentration seem to be risen in Latin America and Caribbean countries with negative economic and political effects at the macro level and in some specific sectors